A Study to assess the effectiveness of planned teaching programme related to home care of acute lymphocytic leukemia (ALL) on knowledge among caregivers of children receiving chemotherapy in selected hospitals of Sangli, Miraj and Kupwad Corporation area - Kale, Aparna (International Journal of Nursing Research, 2023)
Nowadays the acute lymphocytic leukaemia, the most common type of childhood leukaemia, has a very high rate (60- 70%) of survival. Incidence of leukaemia is almost 30% in children. The majority of paediatric cases of acute leukaemia occur below age 5 years. Acute Lymphocytic Leukaemia is most common malignancy accounting for one fourth of all childhood cancer and three fourth of all newly diagnosed patients with leukaemia. To minimize/prevent the symptoms and further consequences a proper home care is needed to the children receiving chemotherapy. This knowledge allows educating and practicing about the home care of children receiving chemotherapy. Based on the above facts the investigators felt the need to implement plan teaching programme in order to improve the knowledge of care givers about the home care of children receiving chemotherapy with Acute Lymphatic Leukaemia as well as to assess the effectiveness of same in terms of caregivers about home care children with Acute Lymphocytic Leukaemia (ALL). The study was conducted in selected hospitals of Sangli-Miraj city. Joshi cancer center, Siddhivinayak Ganpati cancer Hospital, etc. In this study the population consists of care givers of children suffering with acute lymphocytic leukaemia receiving chemotherapy in selected hospitals of Sangli-Miraj and Kupwad corporation area. Sampling technique used in the study was non-probability purposive sampling technique was used. Samples were selected according to the criteria, after obtaining permission from head of the selected hospitals of Sangli, Miraj and Kupwad areas. Study consisted of 40 caregivers of children with ALL receiving chemotherapy in selected hospitals.